HOW TO DEAL WITH DECARBONIZATION – THE ORGANA BIOTECH CASE STUDY - Novais da Silva , Fernando; Zimmermann , Guilherme; Amaral Reinert , Kamili (Revista Gênero e Interdisciplinaridade, 2025)
The decarbonization of the global economy is an urgent imperative to mitigate the impacts of climate change driven by greenhouse gas (GHG) emissions (Rocha; Silva, 2025). In this context, the inadequate management of organic solid waste—historically responsible for methane (CH4) emissions in landfills—remains a critical challenge for the industrial sector. The United Nations Sustainable Development Goal (SDG) 12.3 establishes the need to halve global per capita food waste by 2030, reinforcing the urgency of implementing Circular Economy (CE) practices and waste elimination strategies. This article analyzes the strategic relevance of Organa Biotech, a biotechnology startup based in Joinville (SC), as a pioneering industrial decarbonization case study. Organa Biotech applies an in-company accelerated composting methodology (Takakura Method) combined with data intelligence (gravimetry) to locally transform organic waste into high-quality compost. This approach not only drives waste elimination but also mitigates 1,852 kg of CO2 equivalent per ton of waste diverted from landfills, qualifying as a Clean Development Mechanism. The Organa Biotech model demonstrates an effective and replicable solution for meeting ESG (Environmental, Social, and Governance) criteria (Li et al., 2021) and advancing the productive sector toward carbon neutrality, delivering both economic and environmental value. This work was supported by the Fundação de Amparo à Pesquisa e Inovação do Estado de Santa Catarina (FAPESC), through Public Call Nº 50/2024 – Programa Impulsiona (SC).